If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1x + 17 + 2x = 7 + x Reorder the terms: 17 + 1x + 2x = 7 + x Combine like terms: 1x + 2x = 3x 17 + 3x = 7 + x Solving 17 + 3x = 7 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 17 + 3x + -1x = 7 + x + -1x Combine like terms: 3x + -1x = 2x 17 + 2x = 7 + x + -1x Combine like terms: x + -1x = 0 17 + 2x = 7 + 0 17 + 2x = 7 Add '-17' to each side of the equation. 17 + -17 + 2x = 7 + -17 Combine like terms: 17 + -17 = 0 0 + 2x = 7 + -17 2x = 7 + -17 Combine like terms: 7 + -17 = -10 2x = -10 Divide each side by '2'. x = -5 Simplifying x = -5
| -3-(1-7A)= | | 41x+3+20x=180 | | 43+x=59 | | 6(1+3)=-8(-2+5)-4 | | 82x+9=-99+82x | | 40n^3+48n^2+5n+6= | | 6(5-2x)-2x=86 | | 4z^2+52z=0 | | 18p+90= | | 4x+472=9 | | 3x-[(2x+5)-2(x+3)]+4+x^2=(x+3)(x-5) | | -18=7k+2k | | 17-20x=(-13-5x).4 | | 110+3x-8+3x+6=102 | | 2(m-5)x+2=0 | | 9[w+8]=-7w-24 | | -29=-4x-3(-2x+15) | | 8(j+5)=6 | | 1(x+2)=-3x | | 0+y=11 | | 6g-(g-7)=132 | | -9x-19=-199 | | 23x=60x | | 5(4-2k)-4K=90 | | 6xy-7xy+8x+3=-6y+6 | | 4.8-9.6x= | | 4.50+2.25n=31.50 | | y=3.1x-0.1 | | -5c+4=4 | | -x-3+x=2x-7 | | (1n-8)-(-2+2)= | | -2-6(6b+5)=-248 |